Dendrimers: A Themed Issue in Honor of Professor Donald A. Tomalia on the Occasion of His 80th Birthday - Ashok Kakkar (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Dendrimers have firmly established their space in the macromolecular field since their first discovery in 1978. These monodispersed and hyperbranched macromolecules present unique properties with demonstrated potential in varied scientific disciplines. Dr. Donald A Tomalia is one of the pioneers in this area whose name is synonym for polyamidoamine (PAMAM) dendrimers, one of the most extensively investigated macromolecular architectures. In this monograph, his colleagues and friends celebrate Don's achievements and contributions to the field, on the occasion of his 80th birthday in 2018, which also coincides with the 40th anniversary of the first report on dendrimers. It provides the reader with excellent reviews on different aspects of dendritic architectures, followed by research articles that explore the state-of-the-art in synthesis, properties and varied applications, including in biology. Collectively, it provides scientists just beginning their careers, as well as firmly established ones, with the pulse of the field and inspiration to continue to explore these intriguing macromolecules.